2004
DOI: 10.1080/15216540400008911
|View full text |Cite
|
Sign up to set email alerts
|

Methanococcus vannielii Selenium Metabolism: Purification and N‐terminal Amino Acid Sequences of a Novel Selenium‐binding Protein and Selenocysteine Lyase

Abstract: SummarySelenium is an essential component of several enzymes and proteins in a number of methane-producing archae. Information concerning accessory proteins that function in selenium transport processes, however, is limited. A novel selenium-binding protein with a potential transport role and a selenocysteine lyase that serves as a selenium delivery protein are present in Methanococcus vannielii. The selenium-binding protein was purified from extracts of 75 Selabeled cells. Although there was gradual loss of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Recently, SCL has been shown to be involved in selenoprotein synthesis in vivo in cell culture (193). In addition, in vitro experiments demonstrated that both SPS1 and SPS2 interact with SCL (343) and that bacterial SCL proteins could provide Se to SPS from free Sec, to produce selenophosphate (201,324). These data implicate SCL in the recycling of Se and selenoprotein synthesis.…”
Section: E Sec Lyasementioning
confidence: 75%
“…Recently, SCL has been shown to be involved in selenoprotein synthesis in vivo in cell culture (193). In addition, in vitro experiments demonstrated that both SPS1 and SPS2 interact with SCL (343) and that bacterial SCL proteins could provide Se to SPS from free Sec, to produce selenophosphate (201,324). These data implicate SCL in the recycling of Se and selenoprotein synthesis.…”
Section: E Sec Lyasementioning
confidence: 75%
“…NifS/IscS/SufS-like proteins are also known to abstract Se from selenocysteine (Lacourciere et al 2000;Pilon-Smits et al 2002;Stadtman, 2004), with physiological roles in tRNA and formate dehydrogenase H maturation in bacteria and in the detoxification of selenium in plants Van Hoewyk et al 2005). Thus this family of proteins appears to play a broad role in the mobilization of S and Se within cells.…”
mentioning
confidence: 95%
“…Several of the long range NOEs obtained from four-dimensional 13 C/ 13 C-edited NOESY experiment using uniformly 15 , were also detected in three-dimensional 13 C-edited, 12 Cfiltered NOESY experiments using the mixture of 13 C-labeled subunit and unlabeled subunit, and therefore included in the calculation as intersubunit contacts. The structures converged to a single conformation (Fig.…”
Section: Preliminarymentioning
confidence: 99%
“…In Methanococcus vannielii, the gene corresponding to a family member of these proteins encodes an 8.8-kDa polypeptide. This protein was purified from the organism as a 42-kDa protein and referred to as the selenium-binding protein (SeBP) 3 (12,13). The recombinant protein was shown to bind selenium when the trace element was added to the growth media of the E. coli.…”
mentioning
confidence: 99%